2018
DOI: 10.1136/bmjopen-2017-021080
|View full text |Cite|
|
Sign up to set email alerts
|

Risky business: a longitudinal study examining cigarette smoking initiation among susceptible and non-susceptible e-cigarette users in Canada

Abstract: ObjectivesGiven that many adolescent e-cigarette users are never-smokers, the possibility that e-cigarettes may act as a gateway to future cigarette smoking has been discussed in various studies. Longitudinal data are needed to explore the pathway between e-cigarette and cigarette use, particularly among different risk groups including susceptible and non-susceptible never-smokers. The objective of this study was to examine whether baseline use of e-cigarettes among a sample of never-smoking youth predicted ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 30 publications
2
48
1
2
Order By: Relevance
“…Two mechanisms can be taken into consideration that could explain how exposure to e-cigarette advertisements leads to an increase of tobacco smoking [ 16 ]. One indirect possibility is that through increasing e-cigarette use, the risk for conventional smoking increases [ 11 , 39 ]. There are public health concerns that e-cigarette use may contribute to the development of a new population of cigarette smokers, and act as a “gateway” to future cigarette smoking [ 11 , 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two mechanisms can be taken into consideration that could explain how exposure to e-cigarette advertisements leads to an increase of tobacco smoking [ 16 ]. One indirect possibility is that through increasing e-cigarette use, the risk for conventional smoking increases [ 11 , 39 ]. There are public health concerns that e-cigarette use may contribute to the development of a new population of cigarette smokers, and act as a “gateway” to future cigarette smoking [ 11 , 39 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…One indirect possibility is that through increasing e-cigarette use, the risk for conventional smoking increases [ 11 , 39 ]. There are public health concerns that e-cigarette use may contribute to the development of a new population of cigarette smokers, and act as a “gateway” to future cigarette smoking [ 11 , 39 42 ]. It is not yet fully understood whether e-cigarettes have the potential to cause physical and psychological dependence, but it is assumed that increasing familiarity with nicotine in adolescents used to nicotine consumption might lead to transition to conventional combustible cigarettes because higher doses of nicotine are required to produce the same initial effect [ 11 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some individual-level cohort studies have found a possible causal relationship between prior experience with e-cigarettes and subsequent smoking initiation,18 27–29 including a recent study conducted in Taiwan showing that any e-cigarette use among non-smoking youth at baseline more than doubled the odds that they would initiate cigarette smoking 2 years later 30. Moreover, two Asia-based papers report a significant association between e-cigarette use and heavy smoking among adolescents in Korea31 and Hong Kong 32.…”
Section: Discussionmentioning
confidence: 99%
“…There are recent longitudinal studies on the general population. Many looked at the potential for ECs to introduce young people to smoking (42)(43)(44), con rming reviews that ECs expanded the nicotine market by attracting young people who may later use CCs (11,45). A general population study of adults (18+) in the USA by Benharmina et al (38) showed that ECs may increase the likelihood of tobacco abstinence among those attempting to quit.…”
Section: Introductionmentioning
confidence: 99%